Search for scalar diphoton resonances in the mass range 65-600 GeV with the ATLAS detector in pp collision data at √s=8 TeV. - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Abreu, R; et al. (American Physical Society, 2014)
A search for scalar particles decaying via narrow resonances into two photons in the mass range 65-600 GeV is performed using 20.3  fb(-1) of √s 8 TeV pp collision data collected with the ATLAS detector at the Large Hadron Collider. The recently discovered Higgs boson is treated as a background. No significant evidence for an additional signal is observed. The results are presented as limits at the 95% confidence level on the production cross section of a scalar boson times branching ratio into two photons, in a fiducial volume where the reconstruction efficiency is approximately independent of the event topology. The upper limits set extend over a considerably wider mass range than previous searches.